Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Reef-building corals - Porter, James W. (Washington, D.C. U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.73)
Keywords: Invertebrates; Fishes; History; Corals; Reef-building corals--South Florida